Prevalence and impact of myocardial injury among patients hospitalized with COVID-19 - Vu, Vu Hoang; Nguyen, Thanh Cong; Pham, Quang Dang Duy; Pham, Dan Ngoc; Le, Le Bao; Le, Khoi Minh (Frontiers in Cardiovascular Medicine, 2023)
Background Myocardial injury is a prevalent complication observed in patients hospitalized with COVID-19 and is strongly associated with severe illness and in-hospital mortality. However, the long-term consequences of myocardial injury on clinical outcomes remain poorly understood. This study aimed to assess the impact of myocardial injury on both acute-phase and long-term prognosis in COVID-19 patients. Methods A retrospective, observational study was conducted on all patients who received treatment at the Intensive Care Center for COVID-19 patient, University Medical Center Ho Chi Minh City (UCICC), from August 3rd, 2021, to October 28th, 2021. Results A total of 582 patients were enrolled in the study, of which 55.3% were female. The mean age of participants was 63.3 ± 16.2. Out of these patients, 330 cases (56.8%) showed myocardial injury. Compared to patients without myocardial injury, those with myocardial injury were older and had a higher incidence of chronic diseases including hypertension, ischemic heart disease, atrial fibrillation, heart failure, diabetes mellitus, chronic kidney disease. They also presented with more severe respiratory failure upon admission and showed a more pronounced abnormality in inflammation and kidney function tests. Furthermore, the in-hospital mortality rate was significantly higher in the group with myocardial injury (49.7% vs 14.3%, p < 0.001). After adjusting for age, gender, comorbidities, renal function, and disease severity at admission, myocardial injury emerged as an independent risk factor for in-hospital mortality (OR = 3.758, 95% CI 1.854–7.678, p < 0.001). Among successfully discharged COVID-19 patients, the all-cause mortality rate after a median follow-up of 18.4 months was 7.9%. Patients with myocardial injury had a significantly higher long-term mortality rate compared to those without myocardial injury (14.0% vs. 3.2%, p < 0.001). However, multivariable Cox regression analysis did not find myocardial injury to be a significant predictor of long-term mortality (HR = 2.128, 95% CI 0.792–5.712, p = 0.134). Conclusions Myocardial injury is a common and serious complication in hospitalized COVID-19 patients, associated with increased in-hospital mortality. However, it does not significantly impact long-term mortality in successfully discharged COVID-19 patients.